Kajian Kuat Tekan Beton dengan Penambahan Zat Polymer Sebagai Bahan Pengisi Agregat Terhadap Mutu Beton K-300 (25 MPa) - Siahaan, Desri Yuniarso; Nusa, Ahmad Bima; Dirgantara, Rahmat; Hanova, Yudha; Sari, Kartika Indah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Concrete has now become one of the main materials in buildings that are very important to meet the needs of civil buildings. In various infrastructure buildings in the world, concrete made using portland cement is the biggest material that is most widely used compared to other materials such as steel, wood or bamboo. The concrete industry is the world's largest user of natural resources. Hardened concrete is a combined material consisting of coarse aggregate, fine aggregate, cement and admixture or additives if needed. One way is to replace one of the basic ingredients for making concrete with polymer. A polymer is a long molecule containing chains of atoms linked together through covalent bonds formed through a polymerization process in which monomer molecules react together chemically to form a linear chain or three-dimensional network of polymer chains. The type of polymer used in this test is a recycled polypropylene polymer (plastic pellet). The purpose of this study was to determine the compressive strength of concrete and to determine the slump value of concrete. The effect of adding polymer with variations of 0%, 2% and 4% with a design concrete quality of 25 MPa at the age of 7 days and 28 days. 28 days of concrete reached 25.27 MPa. After researching the effect of adding polymer to the concrete mix can increase the compressive strength of concrete because the test results reach the design quality.